2017
DOI: 10.1039/c6cy00518g
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and bite angle effects in catalytic C–O bond cleavage of a lignin model compound using ruthenium Xantphos complexes

Abstract: Bite angle and electronic effects on the ruthenium–diphosphine catalysed ether bond cleavage of the lignin β-O-4 model compound 2-phenoxy-1-phenylethanol were tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 54 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…As is well-known, ligand participation can promote and regulate organometallic catalysis. , In 2017, Kamer studied the ligand bite angle and electronic effects on the C β –OAr bond cleavage of the β-O-4 models over the Ru–diphosphine catalysts. It was observed that increasing the σ-donor capacity of the ligands can enhance substrate conversion.…”
Section: Organic Molecular Intermediatesmentioning
confidence: 99%
“…As is well-known, ligand participation can promote and regulate organometallic catalysis. , In 2017, Kamer studied the ligand bite angle and electronic effects on the C β –OAr bond cleavage of the β-O-4 models over the Ru–diphosphine catalysts. It was observed that increasing the σ-donor capacity of the ligands can enhance substrate conversion.…”
Section: Organic Molecular Intermediatesmentioning
confidence: 99%
“…They found, using model compounds, that the γ-hydroxy group in the native lignin β-O-4 motif A chelates to the ruthenium-Xantphos complex, trapping and thus deactivating the ruthenium catalyst (Figure b). Since the publication by Bergman and Ellman in 2010, many catalytic systems were developed that can catalyze the same depolymerization reaction sequence on the structurally simplified C2-β-O-4 model compounds representing β-O-4 motif B, but none of these have been reported to be able to effectively depolymerize lignin.…”
Section: Introductionmentioning
confidence: 99%